Integrated Assessment of the Policy of Working Capital Management in Housing and Utilities Enterprises - Poluyanov, V.P.; Palamarchuk, N.S. (Economy of Regions, 2017)
The article describes the approaches to the management of current assets in the enterprises of various industries in economic literature. We discuss theoretical, methodological and applied issues concerning the formation and improvement of the working capital management policy in utility companies, which require further study. The authors propose to assess the policy of working capital management in these enterprises by means of the integrated approach based on the system of reasoned indicators defining the type of working capital management policy. It includes indicators characterizing the policy of working capital management, management of the liquidity of working capital and the policy of financing sources management. The indicators which define the type of the policy of working capital management have been chosen as the most influential for each vector of the improvement of management policy. The range of values is set taking into account the current market conditions for the housing and utilities companies based on theoretical standard values adapted to modern situation. The paper proposes to use an integrated indicator for the evaluation of the policy of working capital management in housing and utilities enterprises. We have substantiated the technique of the integrated assessment of the policy of working capital management in housing and utilities companies. As an example of the application of this indicator, we defined the type of the policy of working capital management in Rostovvodokanal Company. The initial data for the calculation of integrated indicators are the official data on the structure of the balance and financial results of Rostovvodokanal Company during the period from 2012 to 2016. At the Rostovvodokanal Company, it is necessary to bring the type of the policy of working capital management and sources of its financing closer to moderate or conservative type. The authors have substantiated the optimal type of policy of working capital management and the direction for improving the assets management. The proposals, developed in the article are aimed at defining and applying an optimal policy of the working capital management in housing and utilities enterprises in modern conditions. They can be used by other enterprises, industries, government bodies in this sphere.